Детское чтение: 4-5 лет / [художники : Е. Д. Петрова и др.] - Петрова Е. Д. (Скоро в школу!, 2004)
Экземпляры: ф. 3 (20120614) / Инвентарный номер: 98721 / Цена: 60.00 / Авт.знак: Д 38 / ГРНТИ: 17.82 / ББК: 84(0)